PENGARUH PROFITABILITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK - Rostiaty Yunus; Tamsil; Arsyad Paweroi (STKIP Subang, 2025)
This study aims to determine the effect of profitability, leverage and company size on tax avoidance in food and beverage consumer goods industry sector companies listed on the IDX in 2021 - 2023. Tax avoidance is projected using ETR, leverage is measured using the Debt to asset ratio (DAR), profitability is projected using Return On Assets (ROA) and Company size is projected with LN. The sampling technique used is Purposive Sampling with predetermined criteria so that 37 sample data are obtained from 95 selected companies. The data source in this study is secondary data obtained from the company's annual financial report through www.idx.co.id. The data was processed using several stages through classical assumption tests, descriptive statistical analysis methods, multiple linear regression analysis tests, hypotheses (t-test), determination coefficient tests (R2), which were processed using IMB SPSS 26. The results of this study indicate that Profitability has a positive and significant effect on Tax Avoidance, Leverage has a positive but insignificant effect on Tax Avoidance and Company Size has a negative but insignificant effect on Tax Avoidance in companies in the food and beverage consumer goods industry sector listed on the IDX in 2021-2023.